Pengaruh Model Pembelajaran Kooperatif Tipe TGT Terhadap Pembentukan Karakter Peduli Sosial Siswa - Muhammad Husni; Muhammad Sururuddin; Aulia Dwi Hasani; Nia Budi Harti (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The problem in this study is the low social care character of the fifth-grade students at SD Negeri 2 Pohgading. This study aims to analyze the effect of applying the Teams Games Tournament (TGT) cooperative learning model on the social caring character of fifth grade students at SD Negeri 2 Pohgading. This is quantitative research with ex post facto research methods with 41 students of class V SD Negeri 2 Pohgading as population and were 20 VA class students as samples determined using the Purposive Sampling technique. Data collection techniques used interviews, documentation and questionnaires on a scale of five. Data analysis used descriptive statistics and simple linear regression. The results indicate that the cooperative learning model of the TGT type has an effect on the formation of the socially caring character of fifth-grade students at SD Negeri 2 Pohgading with the testing criterion that is if the sig value is 0.00 <0.05 then there is an influence between the X and Y variables or Ho is rejected and Ha is accepted, otherwise the sig value is 0.00 > 0.05. Thus, it is not affected by the variables X and Y or Ha is accepted and Ho is rejected.